An Interview with Professor C.R. Rao on the Occasion of his 100th Birthday - Khanal, Kishor; Khanal, Shankar Prasad (Kathmandu University Journal of Science, Engineering and Technology, 2023)
The late Professor C.R. Rao’s contributions have shaped the theory, application and future of statistics and statistical theory. It is these contributions that have made him a highly respected figure in the academic community. In this email interview, Professor Rao shares valuable insights into statistics and reflects on his passion, expertise and remarkable career in the field.